Neuronal guanine nucleotide exchange factor promotes the axonal growth and cancer cell proliferation via Ephrin-A3/EphA2 axis in lung adenocarcinoma - Jie Mi; Wentian Zhang; Yijiu Ren; Lei Zhu; Bei Yang; Hao Wang; Liang Duan (Journal of Translational Medicine)
Abstract Background Neural infiltration has been found in various cancers and the infiltrating nerves influence tumor growth and dissemination. In non-small cell lung cancer, pan-neuronal marker PGP9.5 was detected by immunohistochemical staining and its high expression correlated with poor prognosis. However, the existence of nerve fibers and the mechanism driving neural infiltration remains unclear. Method We first used immunohistochemical staining to assess the density of nerve fibers in patients with lung adenocarcinoma of different tumor sizes. Following that, we performed differential expression analysis and univariate Cox prognostic analysis, using public datasets and cell experiments to identify the gene that triggers neural infiltration and is associated with cancer progression and unfavorable prognosis. Finally, molecular biology experiments and a subcutaneous tumor model were used to deeply analyze the mechanism that the gene regulates neural infiltration and tumor progression. Results In lung adenocarcinoma patients, the density of PGP9.5 positive nerve fibers within tumors larger than 2 cm in diameter is significantly higher than that in tumors smaller than 2 cm. Bioinformatics analysis suggested NGEF, KIF4A, and PABPC1 could be the genes that trigger neural infiltration and are associated with cancer progression and unfavorable prognosis. Subsequent co-culture experiments with neurons showed that the increased expression of NGEF in lung cancer cells significantly enhanced axonal growth in neurons. Meanwhile, GSE30219 datasets indicated that patients exhibiting high levels of NGEF expression are associated with larger tumor sizes, higher lymph node involvement, and reduced overall survival rates. At the level of molecular mechanisms, the knockdown of Ephrin-A3 in ND7/23 neurons or the use of ALW-II-41-27 resulted in a significant decrease in neurite outgrowth when co-cultured with LA795 cells. In animal model, NGEF overexpression significantly promoted tumor growth and increased the density of nerve fibers, and these effects were inhibited by ALW-II-41-27. Conclusions NGEF facilitates the infiltration of nerve and the growth of cancer cells in lung adenocarcinoma through the Ephrin-A3/EphA2 pathway, suggesting that NGEF is a promising target for disrupting interactions between nerves and tumors. Biomaterials that focus on NGEF are anticipated to be a potential treatment option for lung cancer.